2016
DOI: 10.4236/ojpathology.2016.63014
|View full text |Cite
|
Sign up to set email alerts
|

Pathology Isolation and Identification of Canine Herpesvirus (CHV-1) in Mexico

Abstract: This work presents the pathology description, isolation and identification of canine herpesvirus (CHV-1) in Mexico, a virus that causes a generalized hemorrhagic infection in puppies from the canidae family. Methods: Isolates were obtained from puppies that died within the first four weeks of life and had lesions consistent with canine herpesvirus. Results: The main gross lesions were petechial and ecchymotic hemorrhages in kidneys, liver and lungs; proliferative interstitial nephritis; multifocal necrosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The high prevalence of CHV-1 disease in adult dogs in the central area of Mexico is highly significant when considering that in some areas, our previous research [14] showed that puppies from 1 to 3 months of age were killed by infection, and we were able to isolate strains of the virus. Although the litters belonged to different bitches from those sampled in the present study, our results confirm that canine herpesvirus is present in Mexico, causing clinical infection in newborn puppies and is present in latent form in adults, as has been found in other countries.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The high prevalence of CHV-1 disease in adult dogs in the central area of Mexico is highly significant when considering that in some areas, our previous research [14] showed that puppies from 1 to 3 months of age were killed by infection, and we were able to isolate strains of the virus. Although the litters belonged to different bitches from those sampled in the present study, our results confirm that canine herpesvirus is present in Mexico, causing clinical infection in newborn puppies and is present in latent form in adults, as has been found in other countries.…”
Section: Discussionmentioning
confidence: 95%
“…Because the virus used by us at work has a very low cytolytic effect [14], we employ a combination of routine test SN and observe cytopathic effect of the virus by the detection of cell infection by an immunoperoxidase technique, using antibodies against ca- nine herpes virus of dog and anti canine IgG subsequently antibodies conjugated to peroxidase (Sigma™) developed by diaminobenzidine (Sigma™) on wells with cells [7]. Neutralizing antibodies were tested in 20 randomly selected samples A plaque formation test was used for viral titration.…”
Section: Methodsmentioning
confidence: 99%
“…PCR testing is therefore advocated as a complementary test to confirm active infections (Decaro et al., 2010; Greene et al., 2012; Ledbetter et al., 2009). Conversely, some studies have failed to detect CHV‐1 DNA in dogs despite seroconversion which may be explained by latent infections, sampling methods and assay sensitivity (Bottinelli et al., 2016; Pratelli et al., 2014; Ronsse et al., 2005; Valdivia Lara et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The virus was previously isolated from a 3-day-old dead puppy [6]; Canine Herpesvirus (CHV) was replicated in MDCK cells at a concentration of 10 5 viral particles per ml and was inactivated by UV light exposure, as briefly described; the virus culture was placed in a 54 mm diameter glass Petri dish, capless at a distance of 20 cm from a mercury germicidal lamp (Osram HNS 10W), emitting mainly at 254 nm wavelength light. After 30 min an absorbed dose of approximately of 104 J/m 2 (3.6 quantum/nucleotide) occurred, this UV dose has been described to cause inactivation of alphaviruses and herpesvirus.…”
Section: Methodsmentioning
confidence: 99%